Materiales reciclados y la enseñanza remota en matemática con niños de cinco años de la Institución Educativa Inicial N° 522 Isabel Sandoval Rodríguez, Caballococha 2022 - Trigoso Lopez, Paola Emira (2022)
This research has been developed with the purpose of relating recycled materials and remote teaching in mathematics with five-year-old children from the Initial Educational Institution No. 522 - "Isabel Sandoval Rodríguez", located in the city of Caballo Cocha. The research is relational, with a field, cross-sectional and bivariate design. The population considered was 40 initial-level children, while the sample was from a census. The interview and observation were used as a technique and the questionnaire and an observation guide as an instrument to obtain the data, previously the instruments were validated through expert judgment. The conclusion is that there is a significant relationship between the level of use of recycled materials and remote teaching in mathematics with five-year-old children from the Initial Educational Institution No. 522 - "Isabel Sandoval Rodríguez", in Caballo cocha, because the Kendal's Tau b coefficient = 0.597 indicates that the relationship is direct and high.